Nabiximols effect on blood pressure and heart rate in post-stroke patients of a randomized controlled study - Rosa, Gian Marco; Puce, Luca; Mori, Laura; Currà, Antonio; Fattapposta, Francesco; Porto, Italo; Bragazzi, Nicola Luigi; Trompetto, Carlo; Marinelli, Lucio (Frontiers in Cardiovascular Medicine, 2022)
Background Cannabinoids may be useful to treat pain, epilepsy and spasticity, although they may bear an increased risk of cardiovascular events. This study aims to evaluate the cardiovascular safety of nabiximols, a cannabis-based drug, in patients with spasticity following stroke, thus presenting an increased cardiovascular risk. Methods This is an ancillary study stemming from the SativexStroke trial: a randomized double-blind, placebo-controlled, crossover study aimed at assessing the effect of nabiximols on post-stroke spasticity. Patients were treated with nabiximols oromucosal spray or placebo and assessed before and after two phases of 1-month duration each. Only the phase with the active treatment was considered for each patient who completed the study. The average values of blood pressure (diastolic, systolic, differential) and heart rate from the first 5 days of the phase (lowest nabiximols dosage) were compared to the average values recorded during the last 5 days at the end of the phase (highest nabiximols dosage). Baseline comparisons between gender, stroke type and affected side and correlation between age and blood pressure and heart rate were performed. The study was registered with the EudraCT number 2016-001034-10. Results Thirty-four patients completed the study and were included in the analysis. Thirty-one were taking antihypertensive drugs and, among these, 12 were taking beta-blockers. During the study, no arrhythmic events were recorded, blood pressure and heart rate did not show pathological fluctuations, and no cardiovascular or cerebrovascular events occurred. At baseline blood pressure and heart rate were comparable concerning gender, stroke type and affected side. A significant direct correlation emerged between differential blood pressure and age and an inverse correlation between diastolic blood pressure and age. No correlation emerged between systolic blood pressure or heart rate and age. Blood pressure and heart rate did not change during nabiximols treatment compared to the baseline condition. Conclusion This ancillary study adds evidence that, in patients who already underwent a cerebrovascular accident, nabiximols does not determine significant blood pressure and heart rate variation or cardiovascular complications. These data support the cardiovascular safety of nabiximols, encouraging more extensive studies involving cannabinoids characterized by slow absorption rates.